Optimization of energy use intensity using data envelopment analysis and benchmarking methodology for sustainable rice cultivation under wetland direct seeding conditions in Malaysia - Muazu, Aliyu; Yahya, Azmi; Wan Ishak, Wan Ismail; Bejo, Siti Khairunniza (Universiti Teknologi Malaysia Press, 2016)
Rice is tan important crop and main staple food In Malaysia, The country typically produces about two third of its total requirements with the balance met through import. The imported rice cost less compared to the same grade produce locally. One way to reduce production cost is by improving energy use intensity through optimum use of farm inputs. In this study we investigated the energy use intensity of 40 farms that practices direct seeding system of wetland rice cultivation in Malaysia. At mean yield level of 7,630 kg/ha, the optimum energy use intensity was 1.73 MJ/kg which is lower compared to the energy use intensities in efficient farms, all farms, and the inefficient farms by about 3%, 18% and 26% respectively. Three efficient farms identified as having the highest reference frequency in the study area had a mean yield level of 8,723 kg/ha and a mean energy productivity of 0.642 kg/MJ which were found to be about 1,368 kg/ha (19%) and 0.201 kg/MJ (46%), respectively higher than the mean yield and energy productivity in the inefficient farms. An average farmer in the study area used about 2,914 MJ/ha of energy in excess of the optimum level, representing RM626/ha in lost revenues.